Generalized Epilepsy in Two Patients with 5p Duplication - Kluger, Gerhard; Koehler, Udo; Neuhann, Teresa M.; Pieper, Tom; Staudt, Martin; von Stülpnagel, Celina (Neuropediatrics, 2013)
Background There are only few reports on patients with duplications of the short arm of chromosome 5, with little information about concomitant epilepsy.Patients We report on two patients with generalized epilepsies since age 2.5 years, in whom array comparative genomic hybridization revealed microduplications of different sizes in the short arm of chromosome 5. Both patients showed developmental delay, and magnetic resonance images were normal. The larger duplication in patient 1, who additionally exhibited dysmorphic features and photosensivity on electroencephalogram, occurred de novo, whereas the smaller duplication in patient 2 was paternally inherited.Discussion The overlapping duplicated region in band 5p13.1 comprises four genes (RICTOR, FYB, C9, and DAB2). Further investigation on patients with duplication 5p and epilepsy are needed to possibly identify a potential susceptibility locus for epilepsy at chromosome 5p13.1.
Keywords: 5p microduplication; nonlesional epilepsy; seizures; array CGH